Vanuatu's Support for Papua's Independence Venture - Pratama Dinul Kusuma (Universitas Muhammadiyah Malang, 2022)
Vanuatu is a country that is very vocal and active in providing support for Papua. This can be seen from the efforts made by Vanuatu by raising this issue in several UN council forums. By using the issue of human rights violations in Papua, Vanuatu very regularly attacks Indonesia at every opportunity. This study aims to analyze the support given by Vanuatu for Papuan independence efforts over Indonesia. In international relations, there is always a national interest in relations between states and non-state actors. The research method used in this research is descriptive qualitative with data sources collected through literature studies derived from books, journals, newspapers and other sources. The object of this research is Vanuatu's support, the Papuan independence movement, and the motives for Vanuatu's support for Papua. Data analysis techniques in this study are data reduction, data presentation, and data verification. The results of this study indicate that there are three motives for the support provided by Vanuatu. That are the existence of racial similarities between Vanuatu and Papua, Vanuatu's desire to become the leader of the Asia Pacific region, and the existence of Vanuatu's domestic and foreign political orientations.